The impact of reductants on the catalytic efficiency of a lytic polysaccharide monooxygenase and the special role of dehydroascorbic acid. Issue 1 (12th December 2021) - Stepnov, Anton A.; Christensen, Idd A.; Forsberg, Zarah; Aachmann, Finn L.; Courtade, Gaston; Eijsink, Vincent G. H.
Abstract : Monocopper lytic polysaccharide monooxygenases (LPMOs) catalyse oxidative cleavage of glycosidic bonds in a reductant‐dependent reaction. Recent studies indicate that LPMOs, rather than being O2 ‐dependent monooxygenases, are H2 O2 ‐dependent peroxygenases. Here, we describe Ssc LPMO10B, a novel LPMO from the phytopathogenic bacterium Streptomyces scabies and address links between this enzyme's catalytic rate and in situ hydrogen peroxide production in the presence of ascorbic acid, gallic acid and l ‐cysteine. Studies of Avicel degradation showed a clear correlation between the catalytic rate of Ssc LPMO10B and the rate of H2 O2 generation in the reaction mixture. We also assessed the impact of oxidised ascorbic acid, dehydroascorbic acid (DHA), on LPMO activity, since DHA, which is not considered a reductant, was recently reported to drive LPMO reactions. Kinetic studies, combined with NMR analysis, showed that DHA is unstable and converts into multiple derivatives, some of which are redox active and can fuel the LPMO reaction by reducing the active site copper and promoting H2 O2 production. These results show that the apparent monooxygenase activity observed in Ssc LPMO10B reactions without exogenously added H2 O2 reflects a peroxygenase reaction. Abstract : Lytic polysaccharide monooxygenases (LPMOs) catalyze oxidation of glycosidic bonds in a reductant‐dependent reaction. While it is well known that the nature of the reductant affects LPMO activity, the basis for this connection has remained unclear. Here, we address this issue in detail and investigate LPMO activation by various compounds, including dehydroacrobic acid, which is not considered a reducant but nevertheless fuels LPMO catalysis.